Jules Verne's Legacy between the Literary Imagination and Modernity: Geographical and Historical Perspectives - Duperré, Gustavo Norberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
At the time of including the components of scientific disclosure and adventure stories in the structures of fiction, the Universal Literature found in the leading figure of Jules Verne one of its most genuine exponents. His singularity has transcended his own time, perpetuating the advances of the modern age up to our days, as an unusual notoriety of this French writer. Nevertheless, and beyond the literary imaginary, geographical and historical seasonings are the ones that predominate in the work of Verne, and several of which are part of the famous compilation: Extraordinary Journeys.